Cabbage breeding tools for biotic and abiotic resistance - N. K. Prajapati; Anjali; Ramesh Chand Meena; Razauddin; S. Kumar; P. Kumar; K. Chand (Romanian Journal of Horticulture)
At present, the base for seed potato production is the potato minitubers produced in protected ”insect-proof” spaces. For seed potatoes production it is essential to use a healthy and high-quality biological material, which contributes to obtaining superior productions, both quantitatively and qualitatively. In potato, to eradicate viruses and obtain a healthy initial material, we have at our disposal the technique of sampling and “in vitro” cultivation of meristems. In 2024, 11 potato varieties grown in greenhouses were evaluated. The minitubers derived from "in vitro" cultivated plants. Before micropropagation, the plantlets have been subjected to viral testing using the ELISA technique. Potato microplants used for "in vitro" multiplication were obtained from meristem cultures. Regarding the average number of minitubers/pot, the best results were obtained in Castrum (11.50), Ervant (10.80) and Sevastia (10.10) varieties. The best results in terms of the average weight of minitubers/plant were obtained in Brașovia (271.62 g), Darilena (270.13 g) and Ervant (258.87 g) varieties. The Brașovia and Darilena varieties also recorded the highest values ​​of the average weight of minitubers (53.2 g and 50.92 g, respectively). The highest percentage of minitubers >30 mm (60%) were found for Brașovia and Darilena varieties. Also, for Asinaria, Cosiana, Ervant, Foresta, Marvis and Sarmis varieties, the highest rate was recorded for minitubers in the size fraction 25-30 mm and >30 mm. By selecting appropriate varieties and managing them according to their specific needs, potato growers can enhance the efficiency of seed production systems and achieve higher yields in field multiplication stages.